A policy impact case study using real world data from Welsh government fuel poverty schemes to inform scheme design - Morrison-Rees, Sian; Lowe, Sarah (International Journal of Population Data Science, 2023)
Objectives To reduce fuel poverty in Wales: the Welsh Government developed schemes to provide energy efficiency improvements to lower income households. To inform scheme design: investigate health impacts by linking scheme data to health records. Presented objective: to demonstrate how research findings using real world data can impact policy focus. Approach The research was conducted by an independent researcher at Swansea University who co-produced research questions with the Welsh Government Fuel Poverty Policy Team. A longitudinal dataset was created linking anonymised ‘Warm Homes: Nest’ improvements data to residents’ routine health records in the SAIL Databank at Swansea University. We examined recipient health before and after intervention compared with controls. A high-level policy briefing and research report were published in the Welsh Government Social Research – Analysis for Policy series. Findings were used to design and pilot new eligibility criteria to capture low-income individuals with a respiratory, circulatory or mental health condition. Results This presentation will describe the policy impact pathway from initial discussions with policymakers to real world change, including: securing ESRC funding for a Knowledge Transfer Fellowship, which included a 2013 data linking demonstration project… …which allowed funding to be secured for a 2015-18 research project on the impact of improvements on recipient health… …which published emerging findings in 2016… …and substantive findings in 2017, showing a significant positive impact of improvements on recipient health… …which policymakers used to design a pilot to test ways to widen eligibility criteria to include individuals on a low income with a respiratory, circulatory or mental health condition… …which led to scheme criteria being widened in 2019. By 2021, 25% of recipients entered the scheme via the ‘health route’. Conclusion By delivering research findings generated using linked real world data, and focused on questions co-produced with policymakers, researchers can successfully impact the design and implementation of government policy, thereby improving the lives of people in the real world - in this case, the health of the citizens of Wales.